A preparation process of diamond combination tool

By using a combination technology of carbon nanotubes and cationic silicone dispersant in diamond tools, the problem of insufficient adhesion of diamond coatings is solved, the adhesion and hardness of the tool is improved, the service life is extended and the production cost is reduced. .

CN116288236BActive Publication Date: 2024-12-20HUNAN ANTE ELECTRONIC TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310313656.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2024-12-20
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

When diamond tools process materials such as carbon fiber, the coating is prone to peel off, resulting in unpredictable tool life and insufficient adhesion.

Method used

Carbon nanotubes, diamond particles and cationic silicone dispersants are used to disperse ultrasonically in aqueous ethanol solution. After chemical etching treatment, it is deposited in a hot wire chemical vapor deposition equipment to form a diamond combination tool to improve the adhesion of the coating and density.

Benefits of technology

It enhances the adhesion and hardness of the diamond coating, prevents peeling, improves processing accuracy and tool life, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004149406780000061
    Figure BDA0004149406780000061
  • Figure BDA0004149406780000071
    Figure BDA0004149406780000071
Patent Text Reader

Abstract

The invention discloses a preparation process of a diamond combination tool, which belongs to the technical field of diamond tools, and comprises the following steps: adding carbon nanotubes, diamond particles and a dispersant into an ethanol aqueous solution, and ultrasonically dispersing to obtain a diamond dispersion; chemically etching the substrate after cleaning to obtain a substrate with a negative surface charge, and then placing it into the diamond dispersion for ultrasonic adsorption; placing the substrate after ultrasonic adsorption in a hot wire chemical vapor deposition device for chemical vapor deposition. The substrate is first treated with an alkali and then an acid by using a solution to make the substrate surface negatively charged, and a dispersant is added to the diamond dispersion to make the carbon nanotubes and diamond particles more dispersible. Under this system, electrostatic adsorption is used to increase the adsorption density, and nucleation is performed at a high density on the substrate surface, so that the diamond coating after growth has strong adhesion, prevents the coating from peeling off, is more evenly dispersed, is not easy to generate holes, and is convenient for the subsequent deposition process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diamond tooling, and in particular relates to a preparation process of a diamond combination tooling. Background Art

[0002] Lightweight and high-strength materials are gradually becoming the mainstream. New materials such as non-ferrous metals and alloys, glass fiber reinforced plastics, graphite and ceramics are widely used in industry. Ordinary high-speed steel and carbide tools are not competent for mechanical cutting of these materials. Diamond has extremely stable physical and chemical properties, high hardness and wear resistance, good thermal conductivity and low friction coefficient, etc., which can solve the problems of processing and processing accuracy of difficult-to-process materials. In the existing technology, hot wire assisted chemical vapor deposition technology is used to grow diamond film on the surface of cutting tools to form a diamond coating to improve the processing accuracy of the tool, and it is not limited by the size and shape of the tool.

[0003] When diamond tools are in use, especially when processing materials such as carbon fiber, the coating will peel off. The peeling of the diamond coating is a serious problem for diamond-coated tools, which makes the tool life unpredictable. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation process of a diamond combination tool to solve the problem of insufficient adhesion between the diamond coating and the substrate.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A preparation process of a diamond combination tool comprises the following steps:

[0007] S1. Add carbon nanotubes, diamond particles and dispersant into 90% by volume ethanol aqueous solution, and disperse by ultrasonic for 10-15 minutes to obtain a diamond dispersion;

[0008] S2, chemically etching the substrate after cleaning to obtain a substrate with a negatively charged surface, and then placing it in a diamond dispersion for ultrasonic adsorption;

[0009] S3. Placing the substrate after ultrasonic adsorption in a hot wire chemical vapor deposition device for chemical vapor deposition to obtain a diamond combination tool.

[0010] Furthermore, the usage ratio of carbon nanotubes, diamond particles, dispersant and ethanol aqueous solution is 0.5 g: 5-6 g: 1 g: 100 mL.

[0011] Furthermore, the dispersant is a cationic siloxane; the cationic siloxane is prepared by the following steps:

[0012] Under nitrogen protection, N,N-dimethyl-3-aminopropyltrimethoxysilane and methanol are mixed, the temperature is raised to 55°C, a mixture of epichlorohydrin and methanol is added dropwise, and the reaction is stirred for 6 hours. After the reaction is completed, the methanol is removed by rotary evaporation, and the mixture is washed with ether and dried to obtain a dispersant; the mixture of epichlorohydrin and methanol is a mixture of epichlorohydrin and methanol at a ratio of 1g:10mL, and the molar ratio of N,N-dimethyl-3-aminopropyltrimethoxysilane to epichlorohydrin is 1:1.1.

[0013] Furthermore, the particle size of the diamond particles is 10-100 nm.

[0014] Furthermore, the substrate is one of cemented carbide, stainless steel, silicon nitride and silicon carbide.

[0015] Furthermore, the cleaning process includes the following steps: ultrasonically cleaning the substrate with water for 8-10 minutes, then cleaning with an organic solvent, and drying.

[0016] Furthermore, the organic solvent is a ketone or alcohol solvent; the ketone is acetone; the alcohol is ethanol.

[0017] Furthermore, the chemical etching process is:

[0018] Soak the cleaned substrate in alkaline solution for 10 minutes, take it out and wash it with deionized water and anhydrous ethanol in turn, soak it in acid solution for 10 seconds, take it out and wash it with anhydrous ethanol, and blow it dry with nitrogen.

[0019] Further, the alkali solution is K 3 [Fe(CN)] 6 , KOH and water are mixed in a dosage ratio of 1g:1g:10mL, the acid solution is a mixture of dilute sulfuric acid and hydrogen peroxide in a volume ratio of 1:10, the concentration of dilute sulfuric acid is 1 mol / L, and the mass fraction of hydrogen peroxide is 20%.

[0020] Furthermore, the process parameters of chemical vapor deposition are as follows: methane volume fraction is 2-5%, gas pressure is 0.8-2.5 kPa, temperature range is 1800-2000° C., and processing time is 1-2.5 h.

[0021] Beneficial effects of the present invention:

[0022] In the present invention, the substrate is subjected to an alkali-and-acid corrosion treatment using a specific solution to make the substrate surface negatively charged, and then a dispersant is added to the diamond dispersion to make the carbon nanotubes and diamond particles more dispersible. The particles in the dispersion are positively charged, and in this system, electrostatic adsorption is performed to increase the adsorption density, and high-density nucleation is performed on the substrate surface, so that the grown diamond coating has strong adhesion, prevents the coating from peeling off, is more evenly dispersed, is less likely to generate holes, and is convenient for subsequent deposition processes.

[0023] The dispersant in the present invention is cationic siloxane, in which the silicon element has an sp3 bonding structure, which strengthens the sp3 bonding structure in the film layer, can increase the three-dimensional cross-linking degree, and increase the hardness of the coating.

[0024] In the present invention, a small amount of carbon nanotubes is added as raw materials to the dispersion liquid, so that certain sp3 hybrid bonds can be formed in the carbon nanotubes, and the formed chemical bonds have a mixed hybrid state of sp2 and sp3. The sp3 carbon in the carbon nanotubes is beneficial to improving the nucleation rate of diamond, which can reduce the film forming temperature and the production cost. It can also prevent the increase of sp3 bonding structure, resulting in excessive mismatch in structure and performance between the substrate and the coating, causing the coating to peel off and fail under the action of external force. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] A preparation process of a diamond combination tool comprises the following steps:

[0028] S1. Under nitrogen protection, N,N-dimethyl-3-aminopropyltrimethoxysilane and methanol are mixed, the temperature is raised to 55°C, a mixture of epichlorohydrin and methanol is added dropwise, and the reaction is stirred for 6 hours. After the reaction is completed, the methanol is removed by rotary evaporation, and the mixture is washed with ether and dried to obtain a dispersant; the mixture of epichlorohydrin and methanol is a mixture of epichlorohydrin and methanol according to 1g:10mL, and the molar ratio of N,N-dimethyl-3-aminopropyltrimethoxysilane to epichlorohydrin is 1:1.1; carbon nanotubes, diamond particles and dispersant are added to an ethanol aqueous solution with a volume fraction of 90%, and ultrasonic dispersion is performed for 10 minutes to obtain a diamond dispersion; the amount ratio of carbon nanotubes, diamond particles, dispersant and ethanol aqueous solution is 0.5g:5g:1g:100mL; the particle size of diamond particles is 10-100nm;

[0029] S2, ultrasonically clean the substrate with water for 8 minutes, then clean it with ethanol and dry it; soak the cleaned substrate in alkali solution for 10 minutes, take it out and wash it with deionized water and anhydrous ethanol in turn, soak it in acid solution for 10 seconds, take it out and wash it with anhydrous ethanol, blow it dry with nitrogen; obtain a substrate with negative charge on the surface, then put it into diamond dispersion for ultrasonic adsorption; the alkali solution is K 3[Fe(CN)] 6 , KOH and water are mixed in a dosage ratio of 1g:1g:10mL, the acid solution is a mixture of dilute sulfuric acid and hydrogen peroxide in a volume ratio of 1:10, the concentration of dilute sulfuric acid is 1 mol / L, and the mass fraction of hydrogen peroxide is 20%.

[0030] S3, placing the substrate after ultrasonic adsorption in a hot wire chemical vapor deposition device for chemical vapor deposition, with a methane volume fraction of 5%, a gas pressure of 0.8 kPa, a temperature range of 1800-2000°C, and a processing time of 1 hour; the thickness of the diamond coating is 3-4 μm, and a diamond combination tool is obtained. In this embodiment, the substrate is selected from cemented carbide, specifically YG6 sold on the domestic market.

[0031] Example 2

[0032] A preparation process of a diamond combination tool comprises the following steps:

[0033] S1. Under nitrogen protection, N,N-dimethyl-3-aminopropyltrimethoxysilane and methanol are mixed, the temperature is raised to 55°C, a mixture of epichlorohydrin and methanol is added dropwise, and the reaction is stirred for 6 hours. After the reaction is completed, the methanol is removed by rotary evaporation, and the mixture is washed with ether and dried to obtain a dispersant; the mixture of epichlorohydrin and methanol is a mixture of epichlorohydrin and methanol according to 1g:10mL, and the molar ratio of N,N-dimethyl-3-aminopropyltrimethoxysilane to epichlorohydrin is 1:1.1; carbon nanotubes, diamond particles and dispersant are added to an ethanol aqueous solution with a volume fraction of 90%, and ultrasonic dispersion is performed for 15 minutes to obtain a diamond dispersion; the amount ratio of carbon nanotubes, diamond particles, dispersant and ethanol aqueous solution is 0.5g:6g:1g:100mL; the particle size of diamond particles is 10-100nm;

[0034] S2, ultrasonically clean the substrate with water for 10 minutes, then clean it with ethanol and dry it; soak the cleaned substrate in alkali solution for 10 minutes, take it out and wash it with deionized water and anhydrous ethanol in turn, soak it in acid solution for 10 seconds, take it out and wash it with anhydrous ethanol, blow it dry with nitrogen; obtain a substrate with negative charge on the surface, then put it into diamond dispersion for ultrasonic adsorption; the alkali solution is K 3 [Fe(CN)] 6 , KOH and water are mixed in a dosage ratio of 1g:1g:10mL, the acid solution is a mixture of dilute sulfuric acid and hydrogen peroxide in a volume ratio of 1:10, the concentration of dilute sulfuric acid is 1 mol / L, and the mass fraction of hydrogen peroxide is 20%.

[0035] S3, placing the substrate after ultrasonic adsorption in a hot wire chemical vapor deposition device for chemical vapor deposition, with a methane volume fraction of 4%, a gas pressure of 2kPa, a temperature range of 1800-2000°C, and a processing time of 2h; the thickness of the diamond coating is 3-4μm, and a diamond combination tool is obtained. In this embodiment, the substrate is selected from cemented carbide, specifically YG6 sold on the domestic market.

[0036] Example 3

[0037] A preparation process of a diamond combination tool comprises the following steps:

[0038] S1. Under nitrogen protection, N,N-dimethyl-3-aminopropyltrimethoxysilane and methanol are mixed, the temperature is raised to 55°C, a mixture of epichlorohydrin and methanol is added dropwise, and the reaction is stirred for 6 hours. After the reaction is completed, the methanol is removed by rotary evaporation, and the mixture is washed with ether and dried to obtain a dispersant; the mixture of epichlorohydrin and methanol is a mixture of epichlorohydrin and methanol according to 1g:10mL, and the molar ratio of N,N-dimethyl-3-aminopropyltrimethoxysilane to epichlorohydrin is 1:1.1; carbon nanotubes, diamond particles and dispersant are added to an ethanol aqueous solution with a volume fraction of 90%, and ultrasonic dispersion is performed for 15 minutes to obtain a diamond dispersion; the amount ratio of carbon nanotubes, diamond particles, dispersant and ethanol aqueous solution is 0.5g:6g:1g:100mL; the particle size of diamond particles is 10-100nm;

[0039] S2, ultrasonically clean the substrate with water for 10 minutes, then clean it with ethanol and dry it; soak the cleaned substrate in alkali solution for 10 minutes, take it out and wash it with deionized water and anhydrous ethanol in turn, soak it in acid solution for 10 seconds, take it out and wash it with anhydrous ethanol, blow it dry with nitrogen; obtain a substrate with negative charge on the surface, then put it into diamond dispersion for ultrasonic adsorption; the alkali solution is K 3 [Fe(CN)] 6 , KOH and water are mixed in a dosage ratio of 1g:1g:10mL, the acid solution is a mixture of dilute sulfuric acid and hydrogen peroxide in a volume ratio of 1:10, the concentration of dilute sulfuric acid is 1 mol / L, and the mass fraction of hydrogen peroxide is 20%.

[0040] S3, placing the substrate after ultrasonic adsorption in a hot wire chemical vapor deposition device for chemical vapor deposition, with a methane volume fraction of 2%, a gas pressure of 2.5 kPa, a temperature range of 1800-2000°C, and a processing time of 2.5 hours; the thickness of the diamond coating is 3-4 μm, and a diamond combination tool is obtained. In this embodiment, the substrate is selected from cemented carbide, specifically YG6 sold on the domestic market.

[0041] Comparative Example 1

[0042] Compared with Example 3, this comparative example is different in that the dispersant is replaced with hexadecyltrimethylammonium bromide, and the other raw materials and preparation process remain the same as those of Example 3.

[0043] Comparative Example 2

[0044] Compared with Example 3, this comparative example does not add a dispersant, and the remaining raw materials and preparation process remain the same as those of Example 3.

[0045] Comparative Example 3

[0046] Compared with Comparative Example 2, in this comparative example, no carbon nanotubes are added, and the remaining raw materials and preparation process remain the same as those in Comparative Example 2.

[0047] Performance tests were performed on Example 1-Example 3 and Comparative Example 1-Comparative Example 3:

[0048] Coating adhesion test: Adhesion is determined according to VDI-3198 standard, and the adhesion grades range from HF1 to HF6 from good to bad;

[0049] The NanoTestVantage system was used to characterize the surface hardness (H) of this sample. The indentation depth did not exceed 10% of the coating thickness. Five points were randomly selected and the average value was taken.

[0050] The surface roughness of all samples was characterized using an AxioCSM700 Zeiss white light confocal microscope. The measurement area was 2.5*10 5 μm 2 .

[0051] The results are shown in Table 1:

[0052] Table 1

[0053]

[0054]

[0055] It can be seen from Table 1 that the samples prepared according to the preparation process of the present invention have higher hardness and bonding strength, and have better comprehensive performance than Comparative Examples 1 to 3 in which the type of dispersant is changed, no dispersant is added, and no carbon nanotubes are added.

[0056] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0057] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a diamond combination tool, characterized in that: The steps include: S1, adding carbon nanotubes, diamond particles and a dispersant into an ethanol aqueous solution, and ultrasonically dispersing for 10-15 minutes to obtain a diamond dispersion; the dispersant is a cationic siloxane; S2, chemically etching the substrate after cleaning to obtain a substrate with a negatively charged surface, and then placing it in a diamond dispersion for ultrasonic adsorption; S3. Chemical vapor deposition is performed on the substrate after ultrasonic adsorption to obtain a diamond combination tool.

2. The process for preparing a diamond combination tool according to claim 1, characterized in that: The usage ratio of carbon nanotubes, diamond particles, dispersant and ethanol aqueous solution is 0.5g:5-6g:1g:100mL.

3. The process for preparing a diamond combination tool according to claim 1, characterized in that: The particle size of diamond particles is 10-100 nm.

4. The process for preparing a diamond combination tool according to claim 1, characterized in that: The substrate is one of cemented carbide, stainless steel, silicon nitride and silicon carbide.

5. The process for preparing a diamond combination tool according to claim 1, characterized in that: The cleaning process is as follows: the substrate is cleaned with water ultrasonically for 8-10 minutes, then cleaned with an organic solvent and dried.

6. The process for preparing a diamond combination tool according to claim 5, characterized in that: The organic solvent is a ketone or alcohol solvent.

7. The process for preparing a diamond combination tool according to claim 1, characterized in that: The chemical etching process is: The cleaned substrate was soaked in alkaline solution for 10 minutes, taken out and washed with deionized water and anhydrous ethanol in turn, soaked in acid solution for 10 seconds, taken out and washed with anhydrous ethanol, and blown dry with nitrogen.

8. The process for preparing a diamond combination tool according to claim 7, characterized in that: The alkali solution is a mixture of K3[Fe(CN)]6, KOH and water in a dosage ratio of 1g:1g:10mL, and the acid solution is a mixture of dilute sulfuric acid and hydrogen peroxide in a volume ratio of 1:10, the concentration of the dilute sulfuric acid is 1 mol / L, and the mass fraction of the hydrogen peroxide is 20%.

9. The process for preparing a diamond combination tool according to claim 1, characterized in that: The process parameters of chemical vapor deposition are as follows: methane volume fraction is 2-5%, gas pressure is 0.8-2.5 kPa, temperature range is 1800-2000° C., and processing time is 1-2.5 h.

Citation Information

Patent Citations

  • High-purity nano diamond polishing liquid and preparing method thereof

    CN101033374A

  • Improved case shell of computer

    CN104650713A

  • Preparation method of diamond coating layer, prepared diamond coating layer and cutter

    CN110885968A

  • Dispersant Composition for Carbon Nanotubes, Carbon Nanotube Composite Comprising the Dispersant Composition and Polymer Composite Material Produced Using the Carbon Nanotube C ...

    KR1020120079597A

  • Nanocomposite coatings on cemented carbide

    US20100303564A1